Histomorphological study on prenatal development of the lymphoid organs of native chickens of Bangladesh - Md. Nabiul Islam; Md. Zahirul Islam Khan; Nur Ruboyet Johan; Ryutaro Fujinaga; A. Yanai; K. Kokubu; K. Shinoda (2012)
Native chickens (Gallus domesticus) of Bangladesh are scavenging in nature. Data regarding morphology of lymphoid organs in prenatal stages are lacking. H&E staining method was performed to study the development of the bursa of Fabricius, thymus, spleen and cecal tonsil from embryonic day (ED) 10 to 20. The budding of thymus was seen on ED 10. At ED 12, fiber network of thymus was formed to create a basement of cells of thymus and on ED 14 these cells began to organize to form cortex and medulla. But the cortex and medulla of thymus could not be differentiated before ED 20. The plicae of bursa Fabricius started to develop on ED 10. From ED 12 the plicae became shorter and wider to form bursal follicles and these follicles were clearly organized into cortex and medulla on ED 20. At ED 10, very thin capsule was seen in embryonic spleen. During ED 12, only a few white pulps were observed, while on ED 14, purple colored white pulp and pinkish red pulp were easily visible. At ED 20, the thickness of capsule was increased and pulps were more distinguishable. All the lymphoid organs showed major development during the later incubation period, indicating that the immune system in that period is being prepared to face the scavenging environment after hatching.